Effect of government subsidization on Chinese industrial firms’ technological innovation efficiency: A stochastic frontier analysis - Huang, Qi; Jiang, Marshall S.; Miao, Jianjun (Journal of Business Economics and Management, 2016)
This study aims to gain a better understanding of how effective government subsidization is in helping foster firms’ innovation. Drawing on the exploration/exploita- tion perspective and based on data collected from Statistical Yearbook on Science and Technology Activities of Industrial Enterprises, we look into the relationship between gov- ernment subsidization and Chinese firms’ innovation efficiency by applying a stochastic frontier analysis. The results show that when government subsidies are provided in small scale, firms’ innovation efficiency decreases; only when government subsidies increase to a certain scale, does firms’ innovation efficiency start to increase. We suggest that govern- ment subsidization would generate better innovation performance should it concentrate on a smaller number of firms at one time. As existing research is still inconclusive regarding the relationship between government subsidization and firms’ technological innovation output, we shed light on the issue by revealing a “U-shaped” relationship between the two.